Deep Convection in the Ocean - McWilliams, James C.; Legg, Sonya A. (1999)
Deep-open ocean convection, the process by which vigorous vertical mixing occurs down to great depths in response to wintertime surface buoyancy losses in the sub-polar seas, is a significant mechanism of water mass transformation. The resultant newly mixed deep water masses form a component of the thermohaline circulation, and hence it is essential to understand the deep convection process if the variability of the meridional circulation, and associated climate fluctuations are to be understood. The rates at which the deep water masses are renewed depend on a complex interaction between processes of different spatial and temporal scales, including thermal plumes associated with vertical convection, baroclinic eddies, and larger scale gyre circulations. The mechanism by which these scales of motion interact and lead to mixing in both vertical and horizontal, as well as the rate at which newly mixed water leaves the formation site, are present subjects of considerable uncertainty. Our accomplishments in studying deep convection include: localization of convection by mesoscale preconditioning; demonstration of the energization of barotropic velocity field by convective interaction with pre-existing eddy field; and identification of the role of both eddies and plumes in generating density-compensated tracer variability. Prepared in collaboration with Woods Hole Oceanographic Inst., Woods Hole, MA.